2019
DOI: 10.20944/preprints201911.0187.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Strengthening Participation using Interactive Planning Support Systems: A Systematic Review

Abstract: Interactive Planning Support Systems (PSS) implemented on a maptable are deemed suitable to support participatory planning processes. Through their interactive nature and user-friendly interface they are supposed to facilitate exchange of knowledge between stakeholders, consensus building among them, group learning processes, and thereby strengthen participation. We analyze in this systematic review, based on 16 case studies using interactive PSS, how such PSS have contributed to the goal of strengthening stak… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…There have been several reviews focussed on the development and progress of PSS (15,16,18,(21)(22)(23)(24) and the sectors or elds of application (e.g., land use planning, water management, climate change adaptation) that PSS have been developed for and used in within the domain of spatial planning (25).…”
Section: Introductionmentioning
confidence: 99%
“…There have been several reviews focussed on the development and progress of PSS (15,16,18,(21)(22)(23)(24) and the sectors or elds of application (e.g., land use planning, water management, climate change adaptation) that PSS have been developed for and used in within the domain of spatial planning (25).…”
Section: Introductionmentioning
confidence: 99%
“…An interactive PSS is hardware solutions in the form of digital table combined with geospatial mapping tools specifically dedicated to support group processes (Pelzer et al, 2014). Typically, an application of interactive PSS consists of interactive PSS tools and interactive PSS processes (Flacke et al, 2019). Interactive PSS tool usually consists of large-scale horizontal, touch enabled screen such as MapTable, which allows stakeholders to stand around the table, and a suite of geospatial tool or GIS software for map-based interaction (Figure 1).…”
Section: Interactive Planning Support Systemmentioning
confidence: 99%
“…In a systematic review of interactive PSSs, Flacke et al (2020) found that while stakeholders are involved in the use of the PSSs, in many cases they have minimal input on design of the software systems being used. This distance from the inner workings of the software potentially contributes to them 'far from being used in everyday planning practice'.…”
Section: Introductionmentioning
confidence: 99%
“…In a systematic review of interactive PSSs, Flacke et al. (2020) found that while stakeholders are involved in the use of the PSSs, in many cases they have minimal input on design of the software systems being used.…”
Section: Introductionmentioning
confidence: 99%